Endothelial dysfunction in the post-COVID-19 period: a meta-analysis. (3rd October 2022) - Theofilis, P; Oikonomou, E; Lampsas, S; Siasos, G; Tsioufis, K; Tousoulis, D
Abstract: Background: Coronavirus disease (COVID)-19 is an entity characterized by a cytokine storm and profound endotheliitis. Although several reports have pointed to the presence of endothelial dysfunction in the acute phase, data is accumulating regarding a possible prolonged adverse effect of COVID-19 on endothelial function. Purpose: This systematic review and meta-analysis aims to evaluate the degree of endothelial impairment, assessed by flow-mediated dilation (FMD) of the brachial artery, in individuals recovering from COVID-19. Methods: We conducted a systematic literature search for studies assessing FMD between in patients post-COVID-19 and controls. Exclusion criteria consisted of the absence of a control group, measurement of FMD only during the acute phase of the disease, and not reporting FMD in % change. Effect sizes were pooled via random-effect model and the results are expressed as uncorrected standardized mean difference (SMD), using the Cohen's d as the effect size metric, with 95% confidence intervals (CI). Between-study heterogeneity was assessed through the calculation of I 2 . Subgroup analysis according to follow-up duration and the presence of cardiovascular risk factor-matched controls was also carried out. Results: Database search identified 51 studies. Following the application of the exclusion criteria, 7 studies were included in the meta-analysis (post-COVID-19: 342 subjects, Control: 273 subjects). Compared to controls, patients post-COVID-19 had significantly lower FMD% values (SMD: −1.06, 95% CI: −1.74 to −0.38, p<0.01, I 2 : 86%) (Figure 1). Results remained unaffected after exclusion of any single study using the leave-one-out method. Subgroup analysis revealed no significant differences in FMD between post-COVID-19 patients and controls according to follow-up duration or the presence of cardiovascular risk factor-matched control group. Conclusion: Flow-mediated dilation of the brachial artery, indicative of endothelial dysfunction, was significantly reduced in post-COVID-19 subjects compared to non-infected controls. This finding may be an alarming sign towards a higher risk of incident cardiovascular events. Funding Acknowledgement: Type of funding sources: None.